Antagonism, social critique and the “violent reverie” - Hook, Derek (PINS-Psychology in Society, 2025)
This paper opens up a series of windows on racialised life in past and present South Africa as a way arguing for the value of antagonism as a mode of critical enquiry. Sampling a cross-section of recent writing on South African race politics, the paper calls attention both to strident critiques of white privilege, and to concerns over allegedly anti-white populism. Chabani Manganyi’s notion of the violent reverie is used to argue that such oppositional critique affords a crucial expressive modality, which perhaps unexpectedly, lessens the subjective (self-directed) violence of the historically oppressed and decreases rather than increases the possibility of objective violence between oppressor and oppressed. The paper also draws on a series of philosophical, psychoanalytic and political motifs – the ideas of “no hope”, the Lacanian concept of the imaginary, and Mngxitama’s notion of the failure of interracial dialogue - as a means of drawing attention to the readiness with which we often succumb to comforting social myths.